Katanin catalyzes microtubule depolymerization independently of tubulin C‐terminal tails. Issue 3 (2nd May 2019) - Belonogov, Liudmila; Bailey, Megan E.; Tyler, Madison A.; Kazemi, Arianna; Ross, Jennifer L.
Abstract: Microtubule network remodeling is an essential process for cell development, maintenance, cell division, and motility. Microtubule‐severing enzymes are key players in the remodeling of the microtubule network; however, there are still open questions about their fundamental biochemical and biophysical mechanisms. Here, we explored the ability of the microtubule‐severing enzyme katanin to depolymerize stabilized microtubules. Interestingly, we found that the tubulin C‐terminal tail (CTT), which is required for severing, is not required for katanin‐catalyzed depolymerization. We also found that the depolymerization of microtubules lacking the CTT does not require ATP or katanin's ATPase activity, although the ATP turnover enhanced depolymerization. We also observed that the depolymerization rate depended on the katanin concentration and was best described by a hyperbolic function. Finally, we demonstrate that katanin can bind to filaments that lack the CTT, contrary to previous reports. The results of our work indicate that microtubule depolymerization likely involves a mechanism in which binding, but not enzymatic activity, is required for tubulin dimer removal from the filament ends.